Reimagining Islamic Education Marketing: The Power of Social Media in the Digital Era - Moh. Kamil; Annisa Tri Ananda Dewi; Moh. Jasri (Educazione: Journal of Education and Learning, 2025)
This study aims to analyze the optimization of social media as a marketing instrument for Islamic education in the digital era and to identify effective strategies for improving institutional image, information reach, and public interest in Islamic education services. The research applies a qualitative case study approach using observation, in-depth interviews, and documentation as data collection techniques, with data analyzed through reduction, display, and conclusion drawing. The findings indicate that social media plays a strategic role in expanding promotional reach, strengthening institutional brand image, increasing public engagement, and supporting new student admissions. Platforms such as Instagram, Facebook, TikTok, and YouTube are used to disseminate academic information, religious activities, student achievements, and institutional flagship programs. The effectiveness of digital marketing is influenced by content quality, publication consistency, and the managerial ability to utilize social media features. This study implies that strengthening human resource capacity in digital marketing and developing an integrated digital communication strategy are essential to enhance competitiveness and sustainability of Islamic educational institutions in rapidly evolving information technology era.